Scar endometriosis: a case report - Nain, Poonam; Mehta, Kalpana; Arun, Asmita; Jain, Pragya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Caesarean scar endometriosis is most commonly reported type of abdominal wall endometriosis due to is pathophysiology where endometrial tissue from caesarean incision directly implanted to the scar. A case report of a patient with a troublesome scar after caesarean section is presented below. A 34-year-old multipara with history of caesarean section delivery presented with complain pain, mass and bloody discharge from mass which increases during menstruation since past 5 years with history of lumpectomy 18 months ago with recurrence of symptoms 6 months after lumpectomy. On examination there was a 4×5 cm size, bluish firm, immobile mass at left size of caesarean scar. MRI suggested lesion measures 37×42×45 mm at the paramedian aspect of anterior pelvic wall involving rectus abdominis muscle, subcutaneous tissue and skin at site of previous surgical scar. Patient was operated and histopathological examination confirms diagnosis of scar endometriosis. Scar endometriosis is a rare entity which can easily be misdiagnosed as lump but the cyclic nature of pain with or without discharge from lump in a female patient with history of caesarean section should raise the suspicion of scar endometriosis. Caesarean scar endometriosis has a reported incidence of 0.03 to 0.45%. Diagnosis is mainly clinical after ruling out other conditions and diagnosis can be confirmed with radiology imaging and histopathology. Caesarean scar endometriosis should be considered in a reproductive age group patient with previous caesarean delivery which present with complain of lower abdominal pain.